Production of biosilica based bioactive glass-alginate composite putty as bone support material, and evaluation of in vitro properties; bioactivity and cytotoxicity behavior - Ozarslan, Ali Can; Elalmis, Yeliz Basaran; Yucel, Sevil (ELSEVIER, 2021)
In this study, we prepared biosilica and commercial silica based bioactive glasses with melt-quenching method, and utilized them as the solid phase of composite putties produced using sodium alginate polymer as the liquid phase. Biosilica based and commercial silica based bioactive glass containing composite putties were investigated and compared in terms of rheological features, bioactivity behavior and effect on cell viability. Rheological studies revealed that produced composite putties using both biosilica based and commercial silica based bioactive glasses were both shear thinning (pseudo-plastic) fluids with different consistency coefficient values. Biosilica based and commercial silica based composite putty materials showed differences between each other in terms of bioactivity and did not show any adverse effect on cell viability. Thus, the material features of meltquenched biosilica based bioactive glass/alginate formulations seem relevant for bone tissue engineering applications and biosilica may reduce production costs of these materials.
Keywords: Bioactive glass; biocompatibility; biosilica; bone support; composite putty; sodium alginate; HYALURONIC-ACID; PURE SILICA; TISSUE; SCAFFOLDS; PASTE; SUBSTITUTION; SURFACE; 45S5; Materials Science